PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN AGROBIOFARMAKA BERBASIS KONSERVASI LAHAN DI DESA ILOPONU KABUPATEN GORONTALO - Nurdin Nurdin; Suyono Dude (Universitas Mataram, 2022)
Iloponu Village has the potential for agrobiopharmaceutical development, but has not been developed optimally. The development of agrobiopharmaceuticals is not only beneficial for health but has economic value that can increase people's income. Biopharmaceutical plants such as eucalyptus have the potential to become land conservation plants. This service activity aims to conduct field observations of problems and alternative solutions by implementing participatory technology development and community development, as well as making persuasive and educational efforts to the community in the development of agrobiopharmaceuticals based on land conservation in Iloponu Village. This community service activity uses the following methods: (1) field observation, (2) participatory technology development, (3) community development through training and mentoring, (4) persuasively by jointly building bioprime holes, and (5) educative through the planting of eucalyptus plants together. The development of agrobiopharmaceuticals in the form of making local community medicinal gardens is carried out in locations with priorities for Dusun II, III and IV (priority 1) and Hamlet I (priority 2). Community knowledge and skills increased by more than 80%. Efforts to conserve land based on agrobiopharmaceuticals are carried out together with the community by making biopore holes and planting eucalyptus plants. Field observations help identify problems and set priorities for land conservation-based agrobiopharmaceutical development activities, while participatory technology development has resulted in local community medicine gardens and community development has increased the knowledge and skills of residents in agrobiopharmaceutical development. Persuasive efforts have been carried out by making biopore holes in the yard and agricultural land, while public education has been carried out by planting eucalyptus plants in Iloponu Village.